Evidence-based medicine. Chronic chagas disease grave, with ventricular aneurysm and their treatment - Capuz Eugenio, Rolando Javier; Vivas Vivas, María Leticia (Revista Universidad de Guayaquil, 2010)
Horticultural crops are affected by soil-borne phytopathogens that cause wilting, among them the fungus Sclerotium rolfsii. This phytopathogen reduces yields and contributes to increased production costs due to control measures. The objectives were: 1) To determine the dose of two strains of Trichoderma asperellum on the severity caused by Sclerotium rolfsii in tomato, pepper, and watermelon crops under greenhouse conditions, and 2) To evaluate the methods and times of application of two strains of T. asperellum in these three crops. The dose study treatments were: 1) 5 million spores per plant, 2) 10 million, 3) 15 million, 4) 20 million, 5) 25 million, 6) 30 million spores per plant, 7) Sterile soil, 8) Non-sterile soil, 9) Soil with Captan, 10) Seed with Captan. The application method study had 8 treatments: 1) Applied to the soil surface, seven days before planting, 2) Incorporation into the soil with organic matter and the antagonist seven days before planting, 3) Spraying the antagonist onto the soil seven days before planting, 4) Spraying the antagonist onto the soil seven days after planting, 5) Sterile soil, 6) Non-sterile soil (horticultural field), 7) Soil treated with fungicide, 8) Soil treated with a commercial antagonist. Both experiments were analyzed in a completely randomized design with 10 experimental units. In the dose study, it was determined that 1 x 10^6 conidia of T. asperellum strain G-08 in tomato, pepper, and watermelon crops have an effect in reducing the severity of S. rolfsii infection; on the other hand, strain SE034 with a dose of 15 grams for tomato and pepper crops; in watermelon, 10 grams of substrate. In the application frequency study, T. asperellum strain G-08 for tomato, pepper, and watermelon crops should be applied 7 days before transplanting in liquid form and incorporated with organic matter for preventive treatment and at the first symptoms of the disease for curative treatment, the same procedure should be followed with strain SE034.